Early Poststroke Rehabilitation Using a Robotic Tilt-Table Stepper and Functional Electrical Stimulation. (14th April 2013) - Kuznetsov, Alexey N.; Rybalko, Natalia V.; Daminov, Vadim D.; Luft, Andreas R.
Abstract : Background . Stroke frequently leaves survivors with hemiparesis. To prevent persistent deficits, rehabilitation may be more effective if started early. Early training is often limited because of orthostatic reactions. Tilt-table stepping robots and functional electrical stimulation (FES) may prevent these reactions. Objective . This controlled convenience sample study compares safety and feasibility of robotic tilt-table training plus FES (ROBO-FES) and robotic tilt-table training (ROBO) against tilt-table training alone (control). A preliminary assessment of efficacy is performed. Methods . Hemiparetic ischemic stroke survivors (age58.3 ± 1.2 years, 4.6 ± 1.2 days after stroke) were assigned to 30 days of ROBO-FES (n = 38 ), ROBO (n = 35 ), or control (n = 31 ) in addition to conventional physical therapy. Impedance cardiography and transcranial doppler sonography were performed before, during, and after training. Hemiparesis was assessed using the British Medical Research Council (MRC) strength scale. Results . No serious adverse events occurred; 8 patients in the tilt-table group prematurely quit the study because of orthostatic reactions. Blood pressure and CBFV dipped< 10 % during robot training. In 52% of controls mean arterial pressure decreased by≥ 20 %. ROBO-FES increased leg strength by1.97 ± 0.88 points, ROBO by1.50 ± 0.85 more than control (1.03 ± 0.61, P < 0.05 ). CBFV increased in both robotic groups more than in controls (P < 0.05 ). Conclusions . Robotic tilt-table exercise with or without FES is safe and may be more effective in improving leg strength and cerebral blood flow than tilt table alone.